Structural and theoretical studies of intermolecular dihydrogen bonding in [(C6F5)2(C6Cl5)B]-H···H-[TMP]. - Zaher, H; Ashley, A; Irwin, M; Thompson, A; Gutmann, M; Krämer, T; O'Hare, D (2013)
The product of the intermolecular 'frustrated Lewis pair' (FLP) B(C6F5)2(C6Cl5)/2,2,6,6-tetramethylpiperidine and H2 has been studied by single-crystal neutron diffraction. This is the first structurally characterised example of a geometrically unconstrained dihydrogen (H···H) bond within a hydrogenated FLP system.